Constellation Optimization for MIMO VLC System With Signal-Dependent Noise: Receiver-Side Design and Lookup Table Establishment - Jiaqi Wei; Yuan Wang; Nuo Huang; Yan-Yu Zhang; Yi-Jun Zhu; Wenliang Hao; Chen Gong (IEEE Photonics Journal)
This paper studies the constellation optimization approach for multiple-input multiple-output (MIMO) visible light communication (VLC) systems with signal-dependent noise (SDN). We propose a constellation optimization method aiming at minimizing the system pairwise error probability. In order to obtain the transmitter constellation, we design the demapping rules from the perspective of energy efficiency and illumination uniformity. For the scenario where receiver randomly moves, the constellation lookup table is proposed to transform real-time optimization into table lookup operation, which effectively reduces the real-time computational complexity. Simulation results show that the optimized constellation leads to lower symbol error rate (SER) than the method of maximizing minimum Euclidean distance. In addition, the constellation lookup table operation shows negligible SER performance degradation.